Comprehensive assessment of the Cahora Bassa dam's concrete swelling process - Batista, A. L. (2016)
Cahora Bassa dam is a 170 m high arch dam, of the double curvature type, built in the 1970s on the Zambezi River, in Mozambique. The dam’s concrete is affected by a moderate swelling process, due to alkali-aggregate reactions (AAR) of the alkali-silica (ASR) type, identified in the eighties of the last century, a few years after the construction (1970 to 1975). The owner, the Hidroeléctrica de Cahora Bassa (HCB), in the scope of the general activities of monitoring and safety control, has been increasing the monitoring system and additional testing, to allow a proper characterization of that pathology. The results of laboratorial accelerated expansion tests in samples extracted from the dam´s body, of periodic analysis and the interpretation of the dam´s structural behaviour, based on numerical models of the dam and on the monitoring results, and of regular visual inspections, completed the framework of engineering activities to catch the core knowledge about the swelling phenomenon and its main effects. The paper presents some relevant monitoring results and describes the main procedures related with the safety control activities, in order to allow a comprehensive phenomenon assessment and the correct timely decision making.